Penerapan Model Pembelajaran Picture and Picture Terhadap Hasil Belajar IPA - Ranti Purwanti; Aswarliansyah Aswarliansyah; Candres Abadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the results of science learning for fourth grade students at SD Negeri 29 Lubuklinggau after applying the Picture and Picture learning model. This research method uses an experimental method with a Pre-test and Post-test experimental design, the population is two classes so it uses random sampling where one class is taken randomly with a total of 24 students. The instrument used is in the form of a description of 8 questions. Data collection is taken by test technique. Data were analyzed using the